Substitution between mobile telephony and OTT communication services: the case of Thailand - Monarat Jirakasem; Hitoshi Mitomo (International Telecommunications Society (ITS), 2018)
This research aims to examine the relation between Over-The-Top (OTT) services and mobile telephony. It will also investigate factors affecting customer use of OTT services. Such services have been increasing in terms of revenue and intensity of usage; conversely, revenue from mobile telephony has been declining. As a result, many analysts expect that OTT services may soon replace mobile telephony. Nonetheless, empirical research regarding this assumption is scarce, particularly in the case of Thailand. Thus, this research aims to explore the claim regarding substitution between those two communication services. The research relies on survey data collected in 2014 by NBTC, and comprises 4,716 observations. OTT services in Thailand were found to be complimentary to mobile telephony usage (p-value < 0.001). Furthermore, individuals tend to employ OTT services if they are: female, not married, gaining higher income and education, living in urban areas, owning smartphones, and using international calls. These results are expected to benefit policy makers and the telecommunications field by providing evidence showing that substitution between OTT services and mobile telephony has not occurred in Thailand.
Keywords: 330; Over-The-Top (OTT) services; Mobile telephony; Thailand; Substitution effect